(untitled) (Research, Society and Development, 2022)
Food and Nutrition Security (FNS) is the realization of everyone’s right to regular and permanent access to sufficient quality food without compromising access to other essential needs. The Bolsa Família Program (PBF) benefits millions of families by contributing to the reduction of social inequality, as well as contributing to Brazil’s exit from the Hunger Map. Among the expected effects are the improvement of income, and eating patterns, accompanied by social actions, health and education. This research aimed to describe the food insecurity situation of families benefiting from the Bolsa Familia Program who are cared for in a primary care unit of cariri cearense. The study included mothers / guardians of children between 6 and 23 months of age registered and accompanied by the Family Health Teams (FHS) selected from the municipality of Barbalha and Missão Velha in the state of Ceará. We used a questionnaire on socioeconomic and child health information, the Brazilian Food Insecurity Scale (EBIA). The sample consisted of 132 PBF beneficiary families, with an average per capita of R 193,46; with some degree of food insecurity and with at least 1 address under 18 years. The families studied had a high prevalence of food and nutritional insecurity determined by the low per capita income and the number of residents per household. In addition to high socioeconomic vulnerability even with the transfer of government income through the Bolsa Familia Program.